2000
DOI: 10.1046/j.1365-2796.2000.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Commonly recommended daily intake of vitamin D is not sufficient if sunlight exposure is limited

Abstract: Abstract. Glerup H, Mikkelsen K, Poulsen L, Hass E, Overbeck S, Thomsen J, Charles P, Eriksen EF (University Hospital of Aarhus, and Primary Health Care Centre, City Vest, Aarhus, Denmark). Commonly recommended daily intake of vitamin D is not sufficient if sunlight exposure is limited. J Intern Med 2000; 247: 260±268.Objectives. Sunlight exposure of the skin is known to be the most important source of vitamin D. The aims of this study were: (i) to estimate vitamin D status amongst sunlight-deprived individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
229
0
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(252 citation statements)
references
References 31 publications
(38 reference statements)
12
229
0
11
Order By: Relevance
“…Research to date has indicated that the usual dietary vitamin D intake in Europe is not sufficient to maintain adequate vitamin D status during wintertime when synthesis is minimal (Holick, 1994;Glerup et al, 2000;Ovesen et al, 2003;Hill et al, 2004). The results of the current study support this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Research to date has indicated that the usual dietary vitamin D intake in Europe is not sufficient to maintain adequate vitamin D status during wintertime when synthesis is minimal (Holick, 1994;Glerup et al, 2000;Ovesen et al, 2003;Hill et al, 2004). The results of the current study support this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…In countries around the equator, UV light and, therefore, the production of vitamin D, is constant throughout the year (Glerup et al, 2000). However, seasonal variation in UV intensity, as occurs both far North and South of the equator, results in marked variation in vitamin D status throughout the year, with highest concentrations found in late summer and markedly lower concentrations observed in late winter (McLaughlin et al, 1974;McKenna, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…They calculated that a dose of 400 IU/day would elevate serum 25(OH)D 3 by only 7.0 nmol/l. Several groups have reached the same conclusion, namely that, without appreciable cutaneous synthesis, current cholecalciferol input recommendations are inadequate (Glerup et al, 2000;Vieth et al, 2001). There have been no studies showing toxic effects of higher doses of vitamin D, and Vieth et al (2001) proposed that the evidence available today indicates that a value of 2000 IU/day for the tolerable upper input level is too low.…”
Section: Discussionmentioning
confidence: 99%
“…Les deux conséquences principales de cette nouvelle définition du seuil d'insuffisance en vitamine D sont : l'insuffisance en vitamine D est très fréquente : à des latitudes >408 (l'Europe par exemple) et suivant les populations testées et la période de l'année, 50 à presque 100% des individus ne recevant pas de supplémentation ont une concentration sérique de 25OHD inférieure à 30 ng/mL [77][78][79][80][81][82][83][84] (et Tableau 1) ; les apports nutritionnels conseillés (ANC) pour la vitamine D (400 U/J pour les sujets de moins de 65 ans et 600 U/J pour ceux de plus de 65 ans) sont insuffisants pour atteindre cette cible minimale de 30 ng/mL de 25OHD [85] et il faut donc envisager des doses plus importantes. Il est légitime alors de se poser la question d'un éventuel surdosage.…”
Section: L'étude Des Concentrations Moyennes De 25ohd Atteintes (Quanunclassified